William Howard Taft papers - Taft, William Howard, 1945-
Correspondence, memoranda, speeches, writings, daily records, and other papers documenting Taft's government service in the Richard M. Nixon, Gerald R. Ford, and Ronald Reagan presidential administrations. Documents his work at the U.S. Federal Trade Commission (FTC), Office of Management and Budget (OMB), Dept. of Health, Education and Welfare, and Dept. of Defense, particularly as legal adviser and assistant to Caspar W. Weinberger in many of the latter's cabinet positions. Also includes material relating to Taft's law practice with the firm Leva, Hawes, Symington, Martin and Oppenheimer in Washington, D.C. Subjects include an investigation of the effectiveness of the FTC by consumer advocate Ralph Nader, meetings of the Domestic Council (U.S.) and the Council of Economic Advisers (U.S.), federal-state revenue sharing, effect of an aging population on entitlement programs, presidential impoundment of appropriated funds, tax expenditure analysis, the defense budget, economic effects of the withdrawal of troops from Vietnam, welfare reform, negative income tax, school desegregation, swine flu vaccine liability, and national health insurance.
Family correspondents include Helen Taft Manning, Barbara Hoult Bradfield Taft, John Thomas Taft, Julia Vadala Taft, Robert Taft (1917- ), and William Howard Taft (1915 Aug. 7- ). Other correspondents include Joseph Patrick Addabbo, Les Aspin, Chaplin B. Barnes, Terrel Howard Bell, Peter J. Brennan, Jack Brooks, Jonathan C. Brown, Frank Charles Carlucci, James H. Cavanaugh, Samuel M. Cohn, Lloyd N. Cutler, Robinson O. Everett, Lewis M. Helm, Michael Horowitz, Arthur B. Laffer, Russell B. Long, Forrest David Mathews, William A. Morrill, Tip O'Neill, Richard Norman Perle, Colin L. Powell, Melvin Price, Elliot L. Richardson, William V. Roth, John Derek Schoonmaker, Pat Schroeder, Carl R. Smith, Edward Byron Smith, Peter G. Stillman, David Alan Stockman, Charles M. Super, W. Paul Thayer, Strom Thurmond, John G. Tower, Caspar W. Weinberger, and Joseph Robert Wright.
Library of Congress Prints and Photographs Division.
Lawyer and government official. Known as William Howard Taft IV.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Addabbo, Joseph Patrick, -- 1925-1986 -- Correspondence; Aspin, Les -- Correspondence; Barnes, Chaplin B. -- Correspondence; Bell, Terrel H. -- 1921-1996 -- Correspondence; Brennan, Peter J., -- 1918- -- Correspondence; Brooks, Jack, -- 1922-2012 -- Correspondence; Brown, Jonathan C. -- 1942- -- Correspondence; Carlucci, Frank Charles, -- 1930- -- Correspondence; Cavanaugh, James H. -- 1937- -- Correspondence; Cohn, Samuel M. -- 1915-2005 -- Correspondence; Cutler, Lloyd N. -- Correspondence; Everett, Robinson O. -- Correspondence; Ford, Gerald R., -- 1913-2006.; Helm, Lewis M., -- 1931- -- Correspondence; Horowitz, Michael -- Correspondence; Laffer, Arthur B. -- Correspondence; Long, Russell B. -- Correspondence; Manning, Helen Taft, -- 1891-1987 -- Correspondence; Mathews, Forrest David, -- 1935- -- Correspondence; Morrill, William A. -- 1930- -- Correspondence; Nader, Ralph; Nixon, Richard M. -- 1913-1994.; O'Neill, Tip -- Correspondence; Perle, Richard Norman, -- 1941- -- Correspondence; Powell, Colin L. -- Correspondence; Price, Melvin, -- 1905-1988 -- Correspondence; Reagan, Ronald; Richardson, Elliot L., -- 1920-1999 -- Correspondence; Roth, William V., -- 1921- -- Correspondence; Schoonmaker, John Derek -- Correspondence; Schroeder, Pat -- Correspondence; Smith, Carl R. -- 1933- -- Correspondence; Smith, Edward Byron, -- 1944- -- Correspondence; Stillman, Peter G. -- Correspondence; Stockman, David Alan, -- 1946- -- Correspondence; Super, Charles M. -- Correspondence; Taft, Barbara Hoult Bradfield, -- 1917- -- Correspondence; Taft, John Thomas, -- 1950- -- Correspondence; Taft, Julia Vadala -- Correspondence; Taft, Robert, -- 1917- -- Correspondence; Taft, William Howard, -- 1915 August 7- -- Correspondence; Thayer, W. Paul, -- 1919- -- Correspondence; Thurmond, Strom, -- 1902-2003 -- Correspondence; Tower, John G. -- 1925-1991 -- Correspondence; Weinberger, Caspar W; Weinberger, Caspar W. -- Correspondence; Wright, Joseph Robert, -- 1938- -- Correspondence; Taft family; United States. -- Department of Defense; United States. -- Department of Health, Education, and Welfare; United States. -- Federal Trade Commission; United States. -- Office of Management and Budget; Council of Economic Advisers (U.S.); Domestic Council (U.S.); Leva, Hawes, Symington, Martin and Oppenheimer; Entitlement spending -- United States; Executive impoundment of appropriated funds -- United States; Influenza vaccines; National health insurance -- United States; Negative income tax -- United States